Neuroscience-Based Mindfulness Social Work Practice in Schools. Issue 4 (16th December 2020) - Blundo, Robert; Savage, Tamara Estes
Abstract: Chronic poverty and stressful life circumstances result in poor school performance and behaviors. Research demonstrates that these behaviors are not the result of student inadequacies and lack of proper discipline, but are rather of neurological adaptations to chronic poverty and toxic stress. These outcomes are driven by the body's attempt to protect itself even as the behaviors appear to be choices the student is making in a rational world. Neurobiologically, students adapt to these challenges by becoming both hypersensitive and self-protective. As a result, students are mistrustful and on alert beyond what is usual as a way of protecting themselves, consciously or unconsciously. Mindfulness programs provide important tools for shifting these challenges in the classroom by supporting feelings of safety and opportunities for growth and change in student learning and behaviors. Demonstrating the actual practice of mindfulness is not our intent given that there are many ways of using and learning mindfulness in the classroom. Rather, the focus is on the neurological outcomes of stressful lives, the neurological impact of mindfulness training, and providing resources for addressing student negative experiences and behaviors in schools.